Waste plastics in asphalt concrete: A review - Brian P. Grady (SPE Polymers, 2021)
Abstract Among possible applications for post‐consumer waste plastics, one criterion is that the application should be able to use very large amounts of material because the amount of plastic waste is so large. Another key issue is economics; very little cost should be involved in preparing waste plastics for a specific application. One of the few applications for post‐consumer waste plastics that could possibly meet both requirements is filler in asphalt concrete. Specifically, if waste plastics in asphalt concrete were ∼ 10 wt%, then this application alone could use all plastic waste currently being produced in the world. This review examines the progress that has been made to incorporate waste plastics into asphalt concrete and identifies key issues preventing this technology from being applied commercially.